2012
DOI: 10.1073/pnas.1209919109
|View full text |Cite
|
Sign up to set email alerts
|

Control of cyclooxygenase-2 expression and tumorigenesis by endogenous 5-methoxytryptophan

Abstract: Cyclooxygenase-2 (COX-2) expression is induced by mitogenic and proinflammatory factors. Its overexpression plays a causal role in inflammation and tumorigenesis. COX-2 expression is tightly regulated, but the mechanisms are largely unclear. Here we show the control of COX-2 expression by an endogenous tryptophan metabolite, 5-methoxytryptophan (5-MTP). By using comparative metabolomic analysis and enzyme-immunoassay, our results reveal that normal fibroblasts produce and release 5-MTP into the extracellular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(127 citation statements)
references
References 39 publications
5
121
0
Order By: Relevance
“…In addition, other groups showed that CM from CAFs has a growth-promoting effect on tumor cells due to factors secreted in the culture medium (14,15). Among these factors, IL-6, TGFbeta, COX-2, and CXCL14 have already been mentioned (16)(17)(18)(19)(20). Interestingly, we show that our results are in accordance with Erez et al in that the proinflammatory gene signature was up-regulated in our fibroblasts in vitro as well, except for SPP1, which showed down-regulation upon tumor cell confrontation (21).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, other groups showed that CM from CAFs has a growth-promoting effect on tumor cells due to factors secreted in the culture medium (14,15). Among these factors, IL-6, TGFbeta, COX-2, and CXCL14 have already been mentioned (16)(17)(18)(19)(20). Interestingly, we show that our results are in accordance with Erez et al in that the proinflammatory gene signature was up-regulated in our fibroblasts in vitro as well, except for SPP1, which showed down-regulation upon tumor cell confrontation (21).…”
Section: Discussionsupporting
confidence: 82%
“…29,33,34 On cellular activation, activated NF-κB (p65/ p50) binds to the functional binding sites on the promoter/ enhancer region of diverse genes such as COX-2, iNOS, and proinflammatory cytokines and chemokines. 14,23,25,26,[35][36][37] We show that 5-MTP blocks NF-κB activation that could account for its broad inhibitory actions on the proinflammatory cytokines and mediators. It has been shown that the inhibition of NF-κB is significantly correlated with improvement of survival from endotoxin shock and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that tryptophan hydroxylase 1 (TPH-1) is a key enzyme in 5-MTP synthesis and TPH-1 silencing with siRNA causes reduction of 5-MTP. 14 We wondered whether lipopolysaccharide suppresses 5-MTP through inhibition of TPH-1 expression. TPH-1 proteins were detected in HUVECs that were reduced by lipopolysaccharide in a concentration-dependent manner ( Figure 1F).…”
Section: Ecs Produce 5-mtpmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell invasion assay was performed using 24 Transwell chambers (Corning Inc., Corning, NY, USA) as previously described (14). The single cells were suspended in serum-free RPMI-1640 medium at the concentration of 3x10 5 cells/ml.…”
Section: Rt-pcrmentioning
confidence: 99%